The Effectiveness of Using a Discovery Learning Model Based on Wordwall in Improving Students’ Learning Outcomes - Mutiara Misbah, Nida (Department of Teacher Professional Education, Tarbiya and Teacher Training Faculty, UIN Sunan Gunung Djati Bandung, 2025)
The results of interviews and initial observations found that low learning outcomes in Islamic Religious Education subjects. This condition is caused by various factors, including factors from the environment, teachers and students themselves. This monotonous and less varied learning process makes students quickly feel bored. The lecture and question and answer model that has been used only makes a small proportion of students active. As a result, student learning outcomes are not optimal. The purpose of the study was to determine the effectiveness of the Discovery Learning model based on the Wordwall application on student learning outcomes in Islamic Religious Education subjects. The background of this research is based on the low student learning outcomes due to monotonous conventional learning methods, as well as the lack of student focus during the learning process. This research uses a quantitative approach with a quasi-experimental method with a non-equivalent control group design. The results of the analysis showed that there was a significant increase in the learning outcomes of experimental class students with an average posttest of 78.53 compared to the control class of 68.50. As well as the average N-Gain of the experimental class of 61.2% with the category “quite effective” compared to the control class of 40.1% with the category “less effective”.